Autonomic nervous system dysfunction and their relationship with disease severity in children with atopic asthma - Emin, Ozkaya; Esra, Gursoy; Aysegül, Demir; Ufuk, Erenberk; Ayhan, Sogut; Rusen, Dundaroz M. (Respiratory physiology & neurobiology, 2012)
► The involvement of autonomic imbalance has been reported in the pathogenesis of allergic diseases. ► A comparison of the autonomic nervous system (ANS) testing scores of the control subjects with those of children with asthma revealed significant differences. ► Combined use of HRV and SSR provides a higher degree of sensitivity for assessing disease severity in cases of pediatric asthma. The involvement of autonomic imbalance has been reported in the pathogenesis of allergic diseases. The aim of this study was to investigate the association between the clinical severity of childhood asthma with autonomic nervous system (ANS) dysfunction and to define whether the severity of asthma correlates with ANS activity. In this case–control study, we evaluated the ANS activity by testing heart rate variability (HRV) and sympathetic skin response (SRR) in 77 asthmatic children, age 7–12 yrs, who had no co-morbidity and compared them with 40 gender- and age-matched control subjects. According to the severity of their asthma, study subjects were further divided into three groups: I (mild asthmatics), II (moderate asthmatics), and III (severe asthmatics). Inter-group ANS scale scores differed significantly (p<0.01) between Groups I and III and between Groups II and III. Combined use of HRV and SSR provides a higher degree of sensitivity for assessing disease severity in cases of pediatric asthma.